PENDAMPINGAN PERENCANAAN PENGEMBANGAN USAHA PEMUDA DAN REMAJA MASJID RAUDHATUL JANNAH JEMBER - Dody Wahono Suryo Alam; Supriyanto (BAITUL JUHDI, 2026)
Mosques serve not only as places of worship but also hold significant potential as centers for community empowerment, including in the economic sector. Amidst economic challenges and limited employment opportunities for youth, strengthening entrepreneurial capacity through mosque-based institutions is a crucial strategy for building community independence and economic sovereignty. Based on these conditions, the Community Service Program (PKM) was initiated at the Raudhatul Jannah Mosque in Karangduren Hamlet, Sumberpakem Village, Sumberjambe District, Jember Regency. The main objective of this activity is to assist young people and mosque teenagers in preparing structured productive business development plans, based on Islamic economic values, and contextual to the local potential they have. The method of implementing community service used includes a participatory approach consisting of four main stages: (1) socialization and education of sharia entrepreneurship, (2) training and workshops on preparing business plans, (3) technical guidance on marketing and business management, and (4) intensive field assistance to facilitate the implementation of business ideas. This activity is expected to generate applicable collective business plans, the formation of sustainable mosque youth business groups, and foster a spirit of independence and community-based economic collaboration. This PKM is also expected to become a model for sharia economic empowerment that can be replicated by other mosques in rural areas.